Gender differences in preferences, gateway effects, and potential motivations among e-cigarette users in China - Wei Ji; Liyong Shi; Liyong Shi; Xinjun Lin; Zhiqiang Ji; Zhihuang Zhao; Yanping Chen; Pengxiang Huang; Xiali Wang; Xiaofang Dai; Jing Cheng; Lujun Guo; et al. (Frontiers in Public Health)
ObjectiveA cross-sectional survey was conducted to investigate the differences in preferences, gateway effects, and potential motivations for e-cigarette use among different genders of e-cigarette users in China, thereby providing ideas for the development of public prevention and intervention measures for e-cigarettes.MethodsThis study adopted a combination of online web questionnaires and offline distribution questionnaires to survey 640 e-cigarette users by snowball sampling and convenience sampling in China in 2023. We used the Potential E-Cigarette Dependence Scale, the E-Cigarette Preference Scale, and the General Information Scale to conduct the survey and assessment, and surveyed 360 individuals of those who only used traditional cigarettes for comparison.Results(1) The total number of participants in this research study was 1792, the mean age was 26.9 ± 9.0 years and the number of e-cigarette users was 640, of which 535 (83.6%) were males and 105 (16.4%) were females. (2) There was a statistically significant association between e-cigarette flavor preferences (flavor/nicotine) and gender (p < 0.05). Compared to males, females preferred e-cigarettes with scented/tobacco/fruit/beverage/nicotine (0 mg/12 mg) flavors. (3) Compared with males, females were more likely to “Transition to using traditional cigarettes after smoking e-cigarettes (Gateway effect)” (p < 0.05). (4) Whereas males were more likely to experience “Craving for traditional cigarettes after using e-cigarettes (Induction effect)” (p < 0.05). (5) There were significant gender differences in motivations for e-cigarette use. Males were more likely to use e-cigarettes to “quit traditional cigarettes,” whereas e-cigarette use was more closely related to self-perceptions of “feeling cool.” (6) Multi-factorial logistic regression analysis showed that there was a significant correlation between “e-cigarette liquid flavor (tobacco/fruit/beverage), e-cigarette liquid nicotine concentration (0 mg/12 mg)” and “Gender” (p < 0.05); Gateway effect was significantly correlated with “Gender and Age”(p < 0.05); E-cigarette addiction dependence was not significantly correlated with gender; Mild addiction to e-cigarettes was significantly correlated with “hope e-cigarettes carry nicotine, and the motivations for choosing e-cigarettes (to quit traditional cigarettes)” (p < 0.05). Severe addiction to e-cigarettes was significantly correlated with “hope e-cigarettes carry nicotine, and the motivations for choosing e-cigarettes (unable to use traditional cigarettes in public)” (p < 0.05).ConclusionAmong Chinese e-cigarette users, females preferred e-cigarettes with special flavors, and either without or with middling concentrations of nicotine. The gateway effect was more prominent in females and adolescents, and the induction effect was more notable in males. There was no significant correlation between addiction dependence on e-cigarettes and gender. E-cigarette use was more likely to be motivated by a desire to quit using traditional cigarettes in males, whereas women were more likely to be motivated by “self-perception.”